2003
DOI: 10.1111/j.1572-0241.2003.07297.x
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traveler's Diarrhea Irritable Bowel Syndrome: A Prospective Study

Abstract: This study does not support a large association between TD and an increased risk of developing IBS. A small increase in relative risk may have been undetected because of the size of the study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 9 publications
1
36
0
Order By: Relevance
“…Although Ͻ1% of affected travelers require hospitalization, 80 some studies have shown that 4%-11% of affected travelers develop postinfectious irritable bowel syndrome (PI-IBS). 81,82 Traveler's diarrhea is associated with travel from lowrisk to high-risk regions; risk areas are stratified as low risk (4% risk of developing diarrhea), intermediate risk (15% risk of developing diarrhea), and high risk (40% risk of developing diarrhea). 83 According to the US Centers for Disease Control and Prevention, high-risk regions include Africa (excluding South Africa), South and Central America (excluding Chile and Argentina), as well as most of the Middle East, Southern and Southeast Asia, and Oceania.…”
Section: Traveler's Diarrheamentioning
confidence: 99%
“…Although Ͻ1% of affected travelers require hospitalization, 80 some studies have shown that 4%-11% of affected travelers develop postinfectious irritable bowel syndrome (PI-IBS). 81,82 Traveler's diarrhea is associated with travel from lowrisk to high-risk regions; risk areas are stratified as low risk (4% risk of developing diarrhea), intermediate risk (15% risk of developing diarrhea), and high risk (40% risk of developing diarrhea). 83 According to the US Centers for Disease Control and Prevention, high-risk regions include Africa (excluding South Africa), South and Central America (excluding Chile and Argentina), as well as most of the Middle East, Southern and Southeast Asia, and Oceania.…”
Section: Traveler's Diarrheamentioning
confidence: 99%
“…Chronic diarrhea places a strain on healthcare resources as up to half of travelers returning from tropical and sub-tropical destinations develop infectious diarrhea [14, 6], and an estimated 10 % of those will go on to develop PI-IBS [30]. Despite the prevalence of PI-IBS, this systematic review found only 8 pharmacological and 1 non-pharmacological intervention trials specific to the management of PI-IBS.…”
Section: Discussionmentioning
confidence: 99%
“…Traveler’s diarrhea (TD) is a frequent cause of illness in returning travelers, and it is most often attributable to bacterial causes [13]. It has been well documented that acute gastroenteritis and dysentery due to TD are associated with increased risk of developing post-infectious irritable bowel syndrome (PI-IBS) in both adults and children [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent retrospective study by Chaudhary and Truelove found that a substantial proportion of patients with IBS reported the onset of their symptoms after an acute episode of GE [20] . Since then, various prospective and retrospective studies from the United Kingdom, North America, Spain, Korea, Israel and New Zealand have reported the incidence or prevalence of PI-IBS to range from 5% to 32% [4][5][6][7][8][9][10][11][12][13][21][22][23][24][25] . Consistent among these studies is the suggestion that PI-IBS is a global phenomenon, and not unique to any ethnic group or environment.…”
Section: Epidemiologymentioning
confidence: 99%
“…In some patients, IBS symptoms arise de novo following an exposure to acute gastroenteritis (GE). This phenomenon, known as post-infectious IBS (PI-IBS), denotes the persistence of abdominal discomfort, bloating and diarrhea that continue despite clearance of the inciting pathogen [3][4][5][6][7][8][9][10][11][12][13][14][15] . A recent systematic review and meta-analysis demonstrated that the risk of developing IBS increases six-fold after gastrointestinal infection [16] and remains elevated for at least 2-3 years postinfection.…”
Section: Introductionmentioning
confidence: 99%